EVOLUTION OF BUSINESS ETHICS: FROM GENERAL PHILOSOPHICAL PRINCIPLES TO CORPORATE SOCIAL RESPONSIBILITY - Maryna Dielini (Cхід, 2020)
The article traces the evolution of business ethics from the ideas of simple human responsibility that were put forward by ancient thinkers to complex philosophical moral and ethical, socio-economic constructions on corporate social responsibility. It is noted that in the process of such evolution a whole system of views, judgments and constructions was formed, which should be considered as peculiar stages of further theoretical understanding and expansion of the thematic framework of the phenomenon of “corporate social responsibility”. The analysis showed that the issues of business ethics and social responsibility (and corporate social responsibility as its highest manifestation) have always been most raised in the so-called turning points in the worldview paradigm of human civilization, and the most important theoretical achievements are related to the rationalization of social relations, when the acquired moral and spiritual values were included in the growth of socio-economic resources of society. It is shown that in the 21st century there is a steady demand from business to study the issue of social responsibility, which allows social technologists – representatives of various scientific fields to expand the categorical apparatus, filling new concepts of business ethics, as well as initiate new scientific discussions – valuable principles of society and various pragmatic concepts, the components of which are "principles-process-results".